Capital market liberalization and development (The initiative for policy dialogue series, 2008)
Capital market liberalization has been a key part of the ongoing debate on globalization. Bringing together researchers and practitioners in the field, this book provides an analysis of both the risks associated with capital market liberalization and the alternative policy options available to enhance macroeconomic management.